2017
DOI: 10.1016/j.aller.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IgE-mediated food allergies in children with atopic dermatitis

Abstract: In this study, clinically active food allergies were recognised in 26.13% of children with AD. Nevertheless, no association was confirmed between food sensitisation and AD severity. High IgE and peripheral eosinophilia have not been found more prevalent among children with severe AD nor among children with food sensitisation. Infants and younger children with AD should be screened for an underlying food allergy, regardless of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
16
0
3
Order By: Relevance
“…The increased of serum levels of total IgE in severe atopic patients suggest that IgE levels in the serum of these subjects are associated with increased disease activity in these atopic patients. These results are well supported by previous findings, showed that eczema patients with IgE antibodies against common environmental allergens were at higher risk for the development/progression of atopic disorders especially in pediatric patients [ 33 , 34 ]. The increased levels of IgE observed in the patients with AD, AR or BA in the present study, together with significant increases of filaggrin protein and eosinophil MBP, provide strong evidences of their involvement in these disorders and clearly indicating that filaggrin protein, eosinophil MBP and total IgE are useful in evaluating of AD, AR or BA disease activity, and would therefore be helpful for predicting the progression of these atopic disorders in pediatric patients.…”
Section: Discussionsupporting
confidence: 90%
“…The increased of serum levels of total IgE in severe atopic patients suggest that IgE levels in the serum of these subjects are associated with increased disease activity in these atopic patients. These results are well supported by previous findings, showed that eczema patients with IgE antibodies against common environmental allergens were at higher risk for the development/progression of atopic disorders especially in pediatric patients [ 33 , 34 ]. The increased levels of IgE observed in the patients with AD, AR or BA in the present study, together with significant increases of filaggrin protein and eosinophil MBP, provide strong evidences of their involvement in these disorders and clearly indicating that filaggrin protein, eosinophil MBP and total IgE are useful in evaluating of AD, AR or BA disease activity, and would therefore be helpful for predicting the progression of these atopic disorders in pediatric patients.…”
Section: Discussionsupporting
confidence: 90%
“…In approximately one third of patients, AD is associated with allergic manifestations (e.g. asthma, food allergies, seasonal allergies) 4 , 7 . Recently, associations have also been reported with other inflammatory diseases, including rheumatoid arthritis, inflammatory bowel disease 8 , and systemic lupus erythematosus 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, children with AD often have high serum IgE levels. (26,27) We did not measure total serum IgE on most of our patients. Knowing these values may have helped place some of the sIgE values in better context.…”
Section: Discussionmentioning
confidence: 97%